If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=5/6F-15
We move all terms to the left:
(F)-(5/6F-15)=0
Domain of the equation: 6F-15)!=0We get rid of parentheses
F∈R
F-5/6F+15=0
We multiply all the terms by the denominator
F*6F+15*6F-5=0
Wy multiply elements
6F^2+90F-5=0
a = 6; b = 90; c = -5;
Δ = b2-4ac
Δ = 902-4·6·(-5)
Δ = 8220
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{8220}=\sqrt{4*2055}=\sqrt{4}*\sqrt{2055}=2\sqrt{2055}$$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(90)-2\sqrt{2055}}{2*6}=\frac{-90-2\sqrt{2055}}{12} $$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(90)+2\sqrt{2055}}{2*6}=\frac{-90+2\sqrt{2055}}{12} $
| 3z+15=48 | | 8x-2(3x-5)=24 | | 8(5x-3=6(-3x-4) | | -1/8c=-5/4 | | 2r-3/5=3 | | 3(x-4)=2x=6 | | 6x-12=18-8x | | (4x+9)+(4x+8)+(4x)=(4x)=(4x)+(5x+6) | | 0.7x-0.4(50+x)=-0.1(50) | | 3x+4(x+6)=6x-4x+x | | 4x+8=-4(2x-7)+2x | | 1/3(8x-9)=x+9/6 | | (g/1.9)=10 | | m/3-7=26 | | 4=2c-6/10 | | 10/7=a/6 | | 15x-28=4x | | 6g(2g-1)=13g | | 5x2-60=20 | | -3.7-6x=12.8 | | 4z^2+3z-5=z | | (2w+6)w=228 | | 9-6+u=6+u | | 6x+32=−2x | | 1/2(3x+1)=-4 | | 49x2-16=0 | | -4(r-10)=r+4(1-2r) | | 2h+9=39 | | 6x+20^3-2x=0 | | -5+4n=31 | | 5v-4=39 | | 5x-7x+34=5x+27 |